The lawman's runaway bride - Johns, Patricia (Romance writer) (Johns, Patricia (Romance writer) Comfort Creek lawmen., 2018)
Forced to work with the woman who left his brother at the altar five years ago, police chief Chance Morgan must also face his own guilt. Sadie Jenkins's return to town stirs feelings he thought he'd buried along with his soldier brother, who died overseas. Almost kissing Sadie the night before her wedding was a mistake - one he won't make again. For Sadie, planning a remembrance ceremony for the town's military men will help build her event-planning business. But working with Chance is bringing up all the emotions she once ran from. Is she ready to finally take that leap into the future... with him?